An intervention to decrease patient identification band errors in a children's hospital. Issue 3 (3rd April 2010) - Hain, P D; Joers, B; Rush, M; Slayton, J; Throop, P; Hoagg, S; Allen, L; Grantham, J; Deshpande, J K
Abstract : Context: Patient misidentification continues to be a quality and safety issue. There is a paucity of US data describing interventions to reduce identification band error rates. Setting: Monroe Carell Jr Children's Hospital at Vanderbilt. Key measures: Percentage of patients with defective identification bands. Strategies for change: Web-based surveys were sent, asking hospital personnel to anonymously identify perceived barriers to reaching zero defects with identification bands. Corrective action plans were created and implemented with ideas from leadership, front-line staff and the online survey. Data from unannounced audits of patient identification bands were plotted on statistical process control charts and shared monthly with staff. All hospital personnel were expected to "stop the line" if there were any patient identification questions. Effects of change: The first audit showed a defect rate of 20.4%. The original mean defect rate was 6.5%. After interventions and education, the new mean defect rate was 2.6%. Lessons learnt: (a) The initial rate of patient identification band errors in the hospital was higher than expected. (b) The action resulting in most significant improvement was staff awareness of the problem, with clear expectations to immediately stop the line if a patient identification error was present. (c) Staff surveys are an excellent source of suggestions for combating patient identification issues. (d) Continued audit and data collection is necessary for sustainable staff focus and continued improvement. (e) Statistical process control charts are both an effective method to track results and an easily understood tool for sharing data with staff.